Performance of outbreak management plans for emerging plant diseases: the case of almond leaf scorch caused by Xylella fastidiosa in mainland Spain - Cendoya, Martina; Lázaro, Elena; Navarro-Quiles, Ana; López-Quílez, Antonio; Conesa, David; Vicent, Antonio (APS, 2024)
Outbreak response to quarantine pathogens and pests in the European Union (EU) is regulated by the EU Plant Health Law, but the performance of outbreak management plans in terms of their effectiveness and efficiency has been quantified only to a limited extent. As a case study, the disease dynamics of almond leaf scorch, caused by Xylella fastidiosa (Xf), in the affected area of Alicante, Spain, were approximated using an individual-based spatial epidemiological model. The emergence of this outbreak was dated based on phylogenetic studies, and official surveys were used to delimit the current extent of the disease. Different survey strategies and disease control measures were compared to determine their effectiveness and efficiency for outbreak management in relation to a baseline scenario without interventions. One-step and two-step survey approaches were compared with different confidence levels, buffer zone sizes and eradication radii, including those set by the EU legislation for Xf. The effect of disease control interventions was also considered by decreasing the transmission rate in the buffer zone. All outbreak management plans reduced the number of infected trees (effectiveness) but large differences were observed in the number of susceptible trees not eradicated (efficiency). The two-step survey approach and high confidence level increased the efficiency, while also reducing the transmission rate. Only the outbreak management plans with the two-step survey approach removed infected trees completely, but they required greater survey efforts. Although control measures reduced disease spread, surveillance was the key factor in the effectiveness and efficiency of the outbreak management plans.